Gender Analysis of Mobile Phones Utilization For Agricultural Services Among Farmers In Kwara State, Nigeria - Kayode, Ajoke Oluwatoyin; Awoyemi, Adeseye Oluwasikemi; Oba-Ismail, Basirat Temitope (Universitas Negeri Gorontalo, 2023)
The study analyzed the use of mobiles phones for agricultural services among farming household in Kwara State Nigeria through the gender lens. These objectives were analyzed using descriptive statistics, and multivariate Probit model. Data were obtained from 181 respondents, comprising 96 male farmers and 85 female farmers using a multi-stage sampling procedure, Results reveal the mean age of the male farmers and female farmers as 45 years and 36 years respectively; their average annual income for male and female farmers were â‚¦307,057.97 and â‚¦256,057.69 respectively, Although, male farmers have greater access to land, extension contact, and vast experience in farming than their female counterparts it was confirmed from the results that the level of usage of mobile phones for agricultural services among both gender is high with a mean score of 2.1 for males and 2.0 for females. Male farmers use phones for access to timely and reliable information to support farmers decision making, while majority of the female farmers prefer using their mobile phones in cutting down on travel cost. It was concluded age, household size, years of schooling, income per annum, years of farming experience, and farm size of each gender was a critical factor that influence positively the level of utilization of mobile phones for agricultural services. Policies that address access to the use of mobile phones and other digital technologies for agricultural services should be gender smart.